PENGABDIAN PUBLIKASI KARYA LIMIAH (ARTIKEL DAN PROSIDING) GUGUS V SDN KECAMATAN KARANGPLOSO - Kumala, Farida; Setiawan, Dwi (Jurnal Ilmiah Sekolah Dasar, 2017)
The purpose of this devotional is to conduct training on scientific publication for elementary school teachers of cluster V Karangploso. The benefit of this dedication is to improve the ability of partners in creating an article that can be published results from PTK activities through scientific journals and proceeding. The method of the implementation of this devotion consists of field visits, socialization, training of articles for scientific journals, article-writing training and scientific proceeding power point as well as tips and tricks in selecting scientific journals and proceedings that ended the mentoring and consultation activities. The results of the implementation program is known response from the teacher who has made scientific writing quite well and has produced five articles of service in the form of articles for scientific journals and articles for national and international proceeding. The next plan is to assist in enrolling in national scientific journals as well as international and national seminars.